Imaging tools for holography based particle characterization - Ong, Zhong Kai. (2010)
The morphological forms and habits of specialty chemicals are important properties that can affect the functional properties of the products and also the processing and handling of the products. Therefore it is important to determine the morphological forms of the particles. The morphological forms of the particles can be determined from images captured through photographic or holographic methods. Analysis of these images plays a crucial part in obtaining accurate measurements of the particles. In this project the images handled are images reconstructed from holograms. These images have uneven background pixel intensity that can significantly affect image analysis which in turn affects the measurements of the particles. Therefore to overcome these problems and determine the properties of the particles accurately and efficiently, an algorithm to analyze these images was developed. The information of the particles attained from the algorithm were then calculated and plotted accordingly. The algorithm developed in this paper can also be used on photographic images which are normally better in quality.